ANALISIS PEMBELAJARAN MATA KULIAH ASUHAN KEBIDANAN II PROGRAM STUDI D3 KEBIDANAN UNIVERSITAS ISLAM MADURA: Learning Analysis Courses Of Midwifery Care II Study Program D3 Of Midwifery Islamic University Of Madura - Layla Imroatu Zulaikha; yulia paramita (LPPM - STIKES Pemkab Jombang, 2020)
Background : Midwifery care II is a compulsory subject at study program D3 of midwifery islamic of university of Madura, because it deals directly with the main task of the midwife, is attending births. For that, the learning process of midwifery care II needs special attention, both in term of theory and practice. Objective : The purpose of this study to analyze learning courses of midwifery care II. Method : Design used in this research is descriptive qualitative. Research to be conducted in the from of a single case study with one characteristic (one location). Respondents in this study include student, lectures, and head of study program. In this study there are three kind of data collection analysis. Technical validity of the data with triangulation sources and methode. Techniques used in the analysis process by using interactive analisys model. Result : (1) learning plan is done optimally enough, (2) implementation of learning using of variety of learning methods, (3) evaluations of learning is assesed trough middle test, final test and phase test, (4) contrains encountered in the process of learning that is student interest in learning is less, whereas how to evercome in the learning process are two way communication to determine the dificulty and provide more time for discussion.Conclution : learning process as a whole is less than optimal, because the lack student interest in learning and achivement of learning outcomes is still lacking, it is proved there are 39,59% of the students who have not completed the study with minimum valve of standart campus is 60.